1986
DOI: 10.1515/botm.1986.29.6.503
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Substances from Brown Algae II. Efficiency of Solvents in the Evaluation of Antibacterial Substances from Sargassum johnstonii Setchell et Gardner

Abstract: Four different solvente viz., acetone, diethylether, methanol and ethanol have been used to obtain crude extracts from S. johnstonü and the efficiency of the solvente is tested using gram-positive and gram-negative bacteria. The diethyl-ether extract exhibited Optimum antibacterial activity äs compared with the rest. Six differently preserved samples viz., frozen, shade dried, sun dried, oven dried, fresh and semi-fresh, were extracted with diethyl-ether and the extracts tested against gram-positive and gram-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 11 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…This high inhibition gives a promising indication of developing a potent drug from marine natural sources used in treating human pathogens. Furthermore, the method of extraction, time and place of collecting algal samples, all together, play a critical role in determining the effectiveness of the seaweed extracts in study (Padmini Sreenivasa Rao et al, 1986). Higher antimicrobial activity was revealed with dried seaweeds compared to fresh extracts; lyophilization of algal samples, gives a greater compound extraction; whereas in fresh seaweeds where higher water content is present, produces diluted extracts with lower or even negligible inhibitory activity (Campos-Takaki et al, 1988, Padmini Sreenivasa Rao et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This high inhibition gives a promising indication of developing a potent drug from marine natural sources used in treating human pathogens. Furthermore, the method of extraction, time and place of collecting algal samples, all together, play a critical role in determining the effectiveness of the seaweed extracts in study (Padmini Sreenivasa Rao et al, 1986). Higher antimicrobial activity was revealed with dried seaweeds compared to fresh extracts; lyophilization of algal samples, gives a greater compound extraction; whereas in fresh seaweeds where higher water content is present, produces diluted extracts with lower or even negligible inhibitory activity (Campos-Takaki et al, 1988, Padmini Sreenivasa Rao et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, higher medicinal effect was obtained from dry seaweeds samples than from fresh samples as indicated by many studies which reported that extracts prepared from fresh seaweeds showed negligible antimicrobial activity compared to that obtained from dried seaweeds (Padmini Sreenivasa Rao et al, 1986, Campos-Takaki et al, 1988, Manivannan et al, 2011). In addition, Salvador et al (2007) revealed that algal sample preparation method greatly affect the bioactivity of tested algae (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Marine plants are already known for the antibacterial Raja 2009;Sivaperumal 2009;Muthuraja 2009;Ramanathan and Raju 2000;Naqvi et al 1981;Padmini Sreenivasa Rao et al 1986a), antifungal Naqvi et al 1981;Rao and Shelat 1982;Padmini Sreenivasa Rao et al 1986b), antiviral (Padmakumar and Ayyakkannu 1997;Premanathan et al 1996;Rollet 1981, Balasooriya et al 1982Premanathan et al 1992;Premanathan et al 1993;Naqvi et al 1981), antioxidant (Larson 1988, Masuda et al 1999, antitumor (Hirazumi and Furusawa 1999), anticancer (Jongsuvat 1981), cytotoxicity (Manilal et al 2009;Shehnaz 2003), nematicidal (Manilal et al 2009;Baqar Naqvi et al 1992), antifeedant (Manilal et al 2009), larvicidal (Manilal et al 2009), phytotoxic (Shehnaz 2003), anticoagulant (Anand Ganesh et al 2009) and spermicidal (Prakash 2004) activities, but until recently, no effort has been made to find out the antiplasmodial activity of marine plants.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that compared different treatments are scarce and were carried out on only a few taxa. Campos-Takaki et al (1988) and Padmini Sreenivasa Rao et al (1986) compared fresh and dried algal material; their results also showed lower activity in extracts from fresh tissue than in extracts from dried material. This is probably due to a higher dilution of the bioactive metabolites in the fresh material because of the higher water content.…”
mentioning
confidence: 97%